ASSOCIATION BETWEEN CLINICAL MANIFESTATIONS AND MUTATIONAL VARIANTS OF THE MEFV GENE IN CHILDREN - Hasanova, N.S.; Mammadova, F.M.; Mammadov, S.M.; Hidayatova, L.A. (World of Medicine and Biology, 2025)
The purpose of the study was to assess the clinical characteristics of Familial Mediterranean fever, depending on the variants of genotypic mutations. In total 11 patients with Familial Mediterranean fever aged from 1 to 18 years (mean age 7.4±3.5 years) were involved in the study. The examination included physical, laboratory and instrumental methods. Of the 11 patients with a mutation in the MEFV gene, 55 % had the homozygous M694V variant, 20 % had the homozygous R202Q variant, 15 % had the heterozygous pV726A variant, and 10 % had a compound homozygous R202Q and M694V variant. Patients with the M694V mutation had more severe clinical symptoms (periodic fever, polyserositis), earlier disease onset, and a higher risk of amyloidosis. In the combined variant, 2 boys had phenotypic clinical features of type M694V, as well as elevated paraclinical inflammatory markers and colchicine resistance. Children with heterozygous V726A mutation had abdominal pain, limited in duration fever, and decreased attacks frequency.